Correlation Among Serum Calcidiol, Sun Index, and Vitamin D Intake in Individuals With Seborrheic Keratoses Living in Coastal Area - Izzah Aulia; Larisa Paramitha Wibawa; Lis Surachmiati Suseno; Nurul Ratna Mutu Manikam (Mattioli1885, 2024)
Introduction: Seborrheic keratoses (SK) are benign epidermal tumors with high sun exposure as a major risk factor. Vitamin D deficiency is also thought to play a role in its pathogenesis. There has been no data regarding SK, calcidiol level, vitamin D intake, and sun index (SI) among people living in coastal areas in Indonesia. Objective: To assess the correlation between 1) serum calcidiol levels with SI and vitamin D intake and 2) lesion size with SI and serum calcidiol level among SK patients living in a coastal area. Methods: This is a cross-sectional study. We performed interviews using the sun index questionnaire and semiquantitative food frequency questionnaire for vitamin D; physical examination; dermoscopy to determine the largest SK lesion size; and measurement of serum calcidiol levels in participants with SK living in Cilincing District, North Jakarta. Spearman correlation test was used to assess the relationship between variables. Results: Thirty-nine participants with SK aged 19-59 years old were analyzed. The median of the SK's largest diameter, sun index, serum calcidiol, and vitamin D intake was 2 (1-10) mm, 3.95 (1.1-23.52), 14.3 (5.25-35.30) ng/ml, and 4.3 (0.1-30.1) mcg/day, respectively. Sun index and vitamin D intake were not significantly correlated with calcidiol levels. Similarly, SI and calcidiol levels were not significantly correlated with the largest SK lesion size. Conclusion: We found low calcidiol levels and vitamin D intake in this coastal population. The SI and vitamin D intake had no correlations with calcidiol levels. Furthermore, calcidiol levels and SI had no correlations with the lesion's largest diameter.